Effect of Different Varieties and Types of Organic Fertilizers on The Growth and production of Shallots (Allium ascalonicum L.) - Maulida Maulida; Iswahyudi Iswahyudi; Cut Mulyani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
This study aims to determine the effect of different varieties and types of organic fertilizer on the growth and production of shallots and to determine the interaction between the two. This study used a factorial randomized block design, which consisted of 2 factors, namely: the varietal difference factor (V) which consisted of 3 levels (V1: Sanren variety, V2: Lokananta variety, V3: Bima Brebes variety). The second factor is the type of organic fertilizer (P), which consists of 3 levels (P1: Bioneensis Fertilizer, P2: Atlantic Fertilizer, P3, Chicken Manure). The variables observed in this study were plant height, number of leaves aged 15, 30, 45 and 60 DAP, number of tubers per sample plant, tuber fresh weight per sample plant and per plot, dry tuber weight of plants per sample and per plot. The results showed that the treatment of different varieties gave the best results in the V? treatment (Bima Brebes variety). The results showed that the best results were obtained from P3 treatment (Chicken Manure). There was no interaction between different shallot varieties and the type of organic fertilizer used for all observed research parameters.